Agricultural management strategies for balancing yield increase, carbon sequestration, and emission reduction after straw return for three major grain crops in China: A meta-analysis. (15th August 2023) - Liu, Dantong; Song, Changchun; Xin, Zhuohang; Fang, Chong; Liu, Zhihong; Xu, Yipei
Abstract: Straw return can improve crop yield as well as soil organic carbon (SOC) but may raise the possibility of N2 O and CH4 emissions. However, few studies have compared the effects of straw return on the yield, SOC, and N2 O emissions of various crops. Which management strategies are the best for balancing yield, SOC, and emission reduction for various crops needs to be clarified. A meta-analysis containing 2269 datasets collected from 369 studies was conducted to investigate the influence of agricultural management strategies on yield increase, soil carbon sequestration, and emission reduction in various crops after the straw return. Analytical results indicated that, on average, straw return increased the yield of rice, wheat, and maize by 5.04%, 8.09%, and 8.71%, respectively. Straw return increased maize N2 O emissions by 14.69% but did not significantly affect wheat N2 O emissions. Interestingly, straw return reduced the rice N2 O emissions by 11.43% but increased the CH4 emissions by 72.01%. The recommended nitrogen application amounts for balancing yield, SOC, and emission reduction varied among the three crops, while the recommended straw return amounts were more than 9000 kg/ha. The optimal tillage and straw return strategies for rice, wheat, and maize were plow tillage combined with incorporation, rotary tillage combined with incorporation, and no-tillage combined with mulching, respectively. A straw return duration of 5–10 years for rice and maize and ≤5 years for wheat was recommended. These findings provide optimal agricultural management strategies after straw return to balance the crop yield, SOC, and emission reduction for China's three major grain crops. Graphical abstract: Image 1 Highlights: The yield, SOC, and N2 O of three crops (rice, wheat, and maize) respond differently to straw return. Straw return amounts greater than 9000 kg/ha balance three-grain crops' yield, SOC, and emissions. We recommend straw incorporation for rice and wheat, and mulching for maize. The optimal nitrogen rate and tillage method are dependent on the crops. We recommend a return duration of 5–10 years for rice and maize and ≤5 years for wheat.